A channel-aware reservation protocol for cooperative content distribution over OFDMA networks - Yaacoub, Elias (2011)
In this paper, a channel aware resource reservation protocol for content distribution in an OFDMA wireless network with mobile-to-mobile cooperation is presented. The proposed approach consists of a reservation phase and a transmission phase. The proposed protocol uses channel information in order to avoid unnecessary reservations and thus reduce collisions. The purpose of the proposed protocol is to overcome several practical limitations of the optimal content distribution solution with energy minimization. Simulation results show that the proposed protocol can lead to efficient content distribution between mobile terminals, at the expense of a moderate increase in energy consumption, compared to the optimal solution.